Gender apartheid must be recognized as a crime under international law - Amnesty International (Amnesty International, 2024)
Gender apartheid must be recognized as a crime under international law in order to strengthen efforts to combat institutionalized regimes of systematic oppression and domination imposed on the grounds of gender, said Amnesty International.